Predicting the Winner of Games in World Cup Soccer Matches - Sylla, Mohammed; Magel, Rhonda (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2016)
In this research, statistical models were developed that can be used to predict the outcomes of World Cup soccer matches. Least squares regression and logistic regression techniques were used in the development of the models using data from the 2006 World Cup Matches. The models were tested using data from the 2010 World Cup Matches. Predictions were made for the 2014 World Cup Championship assuming no results were known ahead of time.